The Effect of a Small-Scale Practical Kit and a Practical Instruction Flipbook on Students’ Learning Motivation in Acid-Base Material - Sari, Ely Puspita; Nurjayadi, Muktiningsih; Kurniadewi, Fera (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2025)
This study examines the impact of small-scale practicum kits and flipbook-based instruction on students’ learning motivation in chemistry, specifically in acid–base material. Conducted at SMAN 15 Tangerang Regency, a school with limited laboratory resources, the research employed a quasi-experimental design with a pretest–posttest control group. The experimental group (Class E) utilized small-scale practicum kits and flipbooks, while the control group (Class C) used traditional large-scale laboratory equipment and student worksheets. A total of 34 students in the experimental class and 36 in the control class participated in the study. Data were analyzed using SPSS 26.0, and the statistical tests revealed a significant increase in learning motivation in the experimental group (p = 0.016). The average posttest score for Class E was 60.04, compared to 52.08 for Class C, indicating that the small-scale practicum kits and flipbooks positively influenced students’ motivation. These findings suggest that integrating sustainable and interactive learning tools not only enhances student engagement but also addresses the challenges of resource-limited educational settings. This study contributes to the growing body of literature on the efficacy of small-scale chemistry kits and digital instructional tools in fostering sustainable and inclusive learning experiences in secondary education.